Stress and Resilience in Learning and Life in Islamic Boarding School: Solutions for Soft Approaches to Learning in Modern Times - Muslimah Muslimah; Hamdanah Hamdanah; Abdul Wahab Syakhrani; Arliansyah Arliansyah (Nazhruna: Jurnal Pendidikan Islam, 2019)
This religious study discusses solutions to students' stress and resilience living and studying in Islamic boarding schools from a modern learning approach. To fill in the answers to the above problems, we have reviewed several scientific reports from previous studies with the same theme. Furthermore, the analysis is carried out with a phenomenological approach and in-depth interpretation to restudy the principles of the validity and reliability of the findings. Because this study relies on current data during the pandemic, our search and analysis method was carried out online with the help of the Google search engine, namely keywords including "stress and resilience," "learning in pesantren," "solutions in a gentle approach," " learning in modern times. "So we can summarize our findings, among other things, that of the ten publications we studied, the majority of them had successfully examined students' stress and resilience during their study and stay in an Islamic school environment. This publication shows their social support to advance the world of Muslim education, not yet on the soft skills solution as we expected. Therefore, these findings will provide useful insight for further studies in the future